The research on relationship among online game endorsement, adolescent involvement and game purchase intention - Chao-Sen Wu; Li-Fen Tsai (International Journal of Management, Economics and Social Sciences (IJMESS), 2013)
This research aims to probe the influence of online game endorsement on adolescent involvement and game purchase intention. Involvement means the perceived importance and interest stimulate. The high involvement means consumers will spend more time considering and collecting data in order to make reasonable decision. Data was collected from 366 valid returned questionnaires. The study used Factor Analysis, Correlation, Regression and Mediation Analysis. The research finds that attraction and reliability of online game endorsement significantly and positively influence internal preference and external stimulus of game purchase intention; however, when adolescent involvement is the mediating variable, online game endorsement does not significantly influence game purchase. Thus, this paper suggests that the online game companies should select the suitable game spokespersons and enhance the adolescent's self-judgment.
Keywords: M31; M37; O33; 330; Online game; purchase intention; Adolescent involvement; Self-judgment